Vascular dysfunction in COPD with and without chronic respiratory failure: a cross-sectional study - Paneroni, Mara; Simonelli, Carla; Salvi, Beatrice; Bertacchini, Laura; Vitacca, Michele; Venturelli, Massimo (Frontiers in Physiology, 2026)
BackgroundVascular dysfunction has been described as worsening in Chronic Obstructive Pulmonary Disease (COPD), but there is a lack of knowledge regarding severe patients. This retrospective cross-sectional study aimed to investigate it in COPD with Chronic Respiratory Failure (CRF) versus COPD and controls.MethodsA baseline screening was performed, including a health history, a physical examination, and an anthropometric assessment. All subjects underwent an arterial blood gas analysis, spirometry, a 6-min walking test, and a thigh muscle volume assessment. The vascular function was determined via single Passive Leg Movement (sPLM) on the dominant leg.ResultsFifteen patients with moderate COPD (FEV1 53.3% ± 11.4%), 15 patients with severe COPD (CRF; FEV1 30.6% ± 10.3%), and 15 age-matched healthy controls (CTRL) were recruited. Reactive hyperemia following sPLM was decreased in CRF [peak LBF (Leg Blood Flow) 70 ± 38 mL/min)] compared to COPD (peak LBF 162 ± 115 mL/min) and CTRL (peak LBF 268 ± 134 mL/min), p < 0.05. Interestingly, when the vascular function was normalized to the thigh muscle volume, the difference in the hyperaemic response among the CRF, COPD, and CTRL groups was mitigated but not eliminated. Moreover, the peak LBF was associated with the 6-min walking test (r = 0.7027, p < 0,0001), FEV1 (r = 0.5432, p = 0.0001), disease duration (r = 0.5062, p = 0.0004), oxygen saturation (SpO2) (r = 0.4343, p = 0.0029), and prescribed oxygen flow (r = −0.5413, p < 0.0001).ConclusionThese data provide evidence of an intrinsic vascular dysfunction during the progression of COPD, which depends only partially on locomotor muscle volume loss observed in this clinical population.